Penambahan Bumbu Ketumbar (Cariandrum sativum) dalam Pembuatan Ikan Kering Tawes (Osteochilus sp) - Restu Restu (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2014)
This research aims to learn more about coriander (Cariandrum sativum) seasoning additions to make dried Tawes (Osteochilus sp) fish, so that products have a quality and prefered by consumer. Results of the study showed that the addition of coriander 0.01% of net weight of fish (has been weeding, be salted and added garlic) produces dried tawes fish with specification: protein concentration (46.80 percent); water content (11.69 percent); organoleptic values (7.66). The results of organoleptic were: appearance: intact and clean; smell: typical coriander fregrant; texture: compact and crispy; taste: very delicious specific taste of dried fish. Key words : Dried fish, coriander, Osteochilus sp.